Less training, better improvement: effects of velocity-based complex training on lower-limb maximal strength and explosive performance in highly-trained volleyball athletes - Lin, G.; Deng, B.; Li, Y.; Yan, R.; Li, D.; He, J.; Zhang, X.; Sun, J. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Objectives This randomized controlled trial compared the effects of velocity-based complex training (VBCT) and traditional complex training (TCT) on lower-limb maximal strength and explosive performance in male volleyball athletes during the competitive season.